4. CLINICAL AND ENDOSCOPIC CHARATERISTICS OF PATIENTS WITH GASTRODUODENAL ULCERS AT TIEN GIANG PROVINCE GENERAL HOSPITAL, 2023-2024 (Vietnam Journal of Community Medicine, 2024)
Objective: The study has two objectives: (1) describe the clinical characteristics of Helicobacter pylori-positive peptic ulcer patients, and (2) outline the endoscopic features of these patients at the outpatient department of a provincial general hospital in Tien Giang Province from 2023 to 2024. Methods: A cross-sectional descriptive study was conducted on 148 patients aged 15 and above diagnosed with peptic ulcers due to H. pylori who sought medical care and treatment at the Provincial General Hospital of Tien Giang from 2023 to 2024. Result and conclusion: The most common clinical symptom was epigastric pain, accounting for 92.8% of cases. Endoscopic findings revealed gastric ulcers in 69.7% of patients, duodenal ulcers in 21.4%, and gastroduodenal ulcers in 8.9%. The most frequent site of ulcers was the gastric antrum, comprising 46.4% of cases. Single ulceration was observed in 59.8% of patients, while multiple ulcers were found in 40.2%. Ulcer sizes were less than 5 mm in 32.1% of cases, 5-10 mm in 42%, and greater than 10 mm in 25.9%. The majority of ulcers were round (oval), accounting for 90.2%, while 9.8% were irregularly shaped (erosive ulcers).
Keywords: Peptic ulcer, clinical, endoscopy, patients.